MENJADI GURU SUPER DALAM IMPLEMENTASI PEMBELAJARAN YANG EFEKTIF DAN BERKUALITAS - Asmuki Asmuki; Asrul Anam (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Meaningful learning is learning that can make students understand and think critically. That learning can be created, one of which through the role of super teacher. However, the problem today, there are still many Islamic religious education teachers who are less skilled in teaching, especially in preparing and implementing lessons that are able to generate the enthusiasm of their students. Therefore, the purpose of this discussion to provide an explanation of the terms and characteristics of teachers, patterns of making Muslim educators and their ecosystem, competencies as well as steps to be future super educators.